Horse & Buggy on wheels! - Long, Ethan (Long, Ethan. Horse & Buggy., 2024)
"Horse is ready to try some big skateboard tricks and his best friend Buggy has some tricks of his own on how Horse can avoid getting hurt. From tightening helmet straps to bandaging bruised butts, there's no such thing as too much fun with this dynamic duo--especially because they're playing it safe"--